Analytical methods for assessing the quality of sugarcane bagasse compost and improving the physicomechanical properties toward densification - Ehsan Sarlaki; Mohammad Hossein Kianmehr; Marzieh Ghorbani (علوم محیطی)
Introduction: The stability and maturity indicators of composted biomasses are important to ensure the quality of the final product, maintain consumer confidence, and guarantee safe applicability in agricultural uses. In addition, due to the low energy density and bulk density, the composted biomasses face problems such as higher storage and transportation costs as well as overall costs in logistics management. Particle size reduction and densification of composted biomasses can partially overcome these challenges.Material and methods: Sugarcane bagasse compost (SBC) was prepared from the South bagasse processing development company (Biofer) for quality characterization and assessing the grinding process toward densification. For assessing the quality of SBCs, the physicochemical characterization, as well as the analytical techniques were investigated through differential scanning calorimetry (DSC), X-ray diffraction (XRD), Fourier transform infrared (FT-IR), and scanning electron microscopy (SEM). In the following, a hammer-attrition mill was used to improve the physicomechanical properties and reduce the particle size of SBCs. To this end, an experimental design in the form of factorial design (D-optimal) was used to assess the significance and optimization of the effects of moisture content of SCBs (8, 12, and 16 w.b.%) and screen opening size (1, 2.5, and 4 mm) and rotational speed (1400 and 2000 rpm) of hammer-attrition mill as independent variables on specific energy consumption and bulk density as design responses.Results and discussion: The results obtained from chemical analysis exhibited that the properties of SBCs are in accordance with existing standards. The SEM micrographs revealed a physical change on the surfaces of SBCs with a wrinkly and heterogeneous morphology along with longitudinal cracks with the opening of fiber bundles in cellulose resulting from the degradation of lignin and hemicellulose. This trend was also demonstrated by XRD analysis, so that with increasing the crystallinity index (from 62 up to 75), the crystalline regions of cellulose in SBCs remained unchanged, but the amorphous regions, which includes hemicellulose and lignin, was slightly decomposed. Changes in functional groups from FT-IR spectra demonstrated that the microbial-biological degradation of lipids and carbohydrates, as well as dissociation of lignin and polyphenols occurred in SBCs. From the DSC thermal curves, a glass transition temperature of 89.7 °C was obtained for SBCs, which due to the peak intensity at this point, the improved maturation and humification of SBCs are guaranteed. For both responses of specific energy consumption and bulk density of SBCs, a two-factor interaction (2FI) model with the highest correlation coefficient and the lowest standard deviation was proposed. The mesh opening size had the greatest effect among the parameters on the specific energy consumption and the bulk density.Conclusion: The results demonstrated that the use of comprehensive analytical analyses for an accurate and comparative study between the final composted biomasses and the raw materials in terms of stability and maturity indicators, is practical and reliable. Optimization results from D-optimal design showed that under optimum conditions of moisture content of 8 %w.b, 1-mm mesh opening size and rotational speed 1400 rpm of hammer-attrition mill, a minimum amount of SEC (141.38 KJ/Kg), and the maximum amount of bulk density (209.62 kg/m3) were introduced as optimum responses with the desirability function of 0.88.